PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, SISTEM AKUNTANSI KEUANGAN DAERAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Padangsidimpuan) - Mei Sari Simatupang; Vince Ratnawati; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of the Government Internal Control System, Financial System and the Regional Human Resources Competence of the Effectiveness of Financial Management. This study was conducted in 27 work units City government in Padangsidimpuan. The sample used in this study were 81 respondents. Methods of data collection in this research is survey method with questionnaire delivered directly to the Head of Department, Head of Finance and Treasurer at each SKPD. The analytical method used is multiple regression analysis using the program Statistical Product Service Solution (SPSS). The test results show that the internal control systems of government affect the effectiveness of financial management, with a regression coefficient of 2.355 and a significance level of 0,016. The area of financial accounting system affect the effectiveness of financial management with a regression coefficient of 2.254 and a significance of 0.015. Competence of human resources affect the effectiveness of financial management with a regression coefficient of 3.503 and a significance of 0.001. While the coefficient of determination is 0.179, which means 17,9% of independent variables affect the dependent variable. While 82,1% is influenced by other variables not included in this study.Keywords : Internal Control, Financial Accounting, Competenc, and Effectiveness